2005
DOI: 10.1111/j.1742-4658.2005.05027.x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic transformations of supercoiled DNA as studied by flow linear dichroism technique

Abstract: The dynamic of supercoiled DNA (scDNA) transformations is the key point for understanding the numerous processes taking place in the living cell [1]. DNA topology changes are vital in replication, transcription, recombination, chromosome condensation, and segregation. From the topological point of view DNA can be represented as a closed ribbon [2][3][4]. A study of the dynamic aspects of the DNA topology is closely associated with a design of an adequate mathematical description of the DNA polymeric molecule a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The maximal theoretical response was calculated according to the molecular masses of the human ATPase domain and ligands 8 and 12. [49] This promising new approach could complement the SPR studies, offering further insight into the inhibition process of our discovered compounds. We were pleased to establish that K D values for both compounds 8 and 12 were in good agreement with the determined IC 50 inhibitory activity values (Table 4).…”
Section: Spr Measurementsmentioning
confidence: 94%
See 1 more Smart Citation
“…The maximal theoretical response was calculated according to the molecular masses of the human ATPase domain and ligands 8 and 12. [49] This promising new approach could complement the SPR studies, offering further insight into the inhibition process of our discovered compounds. We were pleased to establish that K D values for both compounds 8 and 12 were in good agreement with the determined IC 50 inhibitory activity values (Table 4).…”
Section: Spr Measurementsmentioning
confidence: 94%
“…It should be noted that, recently, a powerful flow linear dichroism (FLD) technique for continuous monitoring of the topoisomerization reaction was reported, enabling in-depth mechanistic studies of topo enzymes and their interactions with ligands. [49] This promising new approach could complement the SPR studies, offering further insight into the inhibition process of our discovered compounds.…”
Section: Spr Measurementsmentioning
confidence: 94%
“…Various reactive oxygen species (ROS) can participate in the DNA cleaving process [47][48][49][50]. Lanes 3-6 in Figure 5 shows the effect of ROS scavengers on scDNA cleavage.…”
Section: Effect Of Reactive Oxygen Scavengersmentioning
confidence: 99%
“…It had been found that undigested foods in the large intestine change into toxic substances that could reduce the life span and cause cancer. Thus, patients were advised to follow zero food diets to get rid of these unpleasant materials and take a break from digestion activities (33).…”
Section: What Is Nutrition Science?mentioning
confidence: 99%